1977
DOI: 10.1080/00102207708946825
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis on Flame Stabilization by a Bluff-Body

Abstract: A simplified analysis has been attempted on flame stabilization by bluff-body based on a physical model. The proposed theoretical model predicts with fair accuracy the experimental results of Zukoski and Marble (1956), Fetting et al. (1959) and also of the present investigation. Implications of theoretical and experimental results have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…In addition, Kundu et al's. [100,101] measurements show a monotonic reduction of temperature in the recirculation zone as the flow velocity increases toward its blowoff value. They found that the ratio of wake to adiabatic flame temperature decreased from 0.94 to 0.88 as U/U LBO increased from 0.3 to 0.9.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Kundu et al's. [100,101] measurements show a monotonic reduction of temperature in the recirculation zone as the flow velocity increases toward its blowoff value. They found that the ratio of wake to adiabatic flame temperature decreased from 0.94 to 0.88 as U/U LBO increased from 0.3 to 0.9.…”
Section: Discussionmentioning
confidence: 93%
“…Since entrainment rates scale as D/U (see Section 2.2.2) then it follows that this criterion reduces to a Damkö hler number blowoff criterion, using a chemical time that is derived from the well stirred reactor, s PSR . A similar idea relates to an energy balance between heat supplied by the hot recirculating flow to the fresh gases and that released by reaction [98,[100][101][102]. In this view, blowoff occurs when the heat required by the combustible stream exceeds that received from the recirculation zone.…”
Section: Discussionmentioning
confidence: 98%
“…The total mass flow rate of air contained in the freestream is not appropriate because this flow rate can be made arbitrarily large by increasing the height of the freestream above the recirculation zone, and this height is not a relevant parameter. Winterfeld 6 and Kundu et al 4 present data showing that the air mass flow rate entrained into a recirculation zone behind a bluff body of height H and width W is proportional to ρ A U A H W . Therefore, following the convention set by Winterfeld, 7 the characteristic air mass flow rate is defined as…”
Section: Correlation Of Blowout Limits For Nonpremixed Flamesmentioning
confidence: 97%
“…Spalding [10] and Kundu et al [11] studied the role of the recirculation zone on blowout criteria. Nicholson and Field [12] and Chao et al [13] reported increased flame detachment and reattachment events near blowout.…”
Section: Blowout Phenomenonmentioning
confidence: 99%